A Novel Phenotype of the Factor 5 Gene Mutation (Homozygote Met1736Val and Heterozygote Asp68His) Is Associated With Moderate Factor V Deficiency - Chang, Yueh-Shih; Lan, Yi-Cheng; Chen, Ya-Jyun; Huang, Jen-Seng; Yang, Chia-Ning; Huang, Chi-Ying F.; Yeh, Kun-Yun (Frontiers in Medicine, 2022)
Background: Factor V (FV) deficiency is a rare disease and more prevalent in Western countries than in Asia. Therefore, the FV mutation in the Chinese population is poorly understood. Methods: A Chinese family with FV deficiency was included, and a mutation screening of the patient and family members was conducted. Then, patients from Keelung City (Taiwan) were screened for FV polymorphism; the Chang Gung Human Database was used to determine single-nucleotide variants (SNVs) in the non–FV-deficient patient population. Results: Eight mutation sites on the FV gene locus, including exon 16 homozygote Met1736Val, and other seven heterozygote mutations, including A68His, were found. Moreover, Met1736Val is the dominant mutation in people living in the Keelung area, which was compared with the records from the Chang Gung Human Database. This report shows possible pre-prognosis of FV mutations and polymorphisms in Taiwanese patients, facilitating carrier diagnosis and prenatal diagnosis in most FV-deficient families. Conclusion: The homozygote M1736V and the co-inheritance of the A68His FV gene is unique and worthy of screening for FV-deficient patients.